Class III Correction With Reverse Twin Block—A Case Report - Sushant Pandey; Rajesh Gyawali; Prabhat Ranjan Pokharel; Avinash Chaudhary; Samikshya Sangroula (Clinical Case Reports)
ABSTRACT The orthodontic management of patients with Class III malocclusion poses numerous treatment challenges. Various removable, fixed, orthopedic, and myofunctional appliances have been recommended for its correction. The Reverse Twin Block is a removable appliance which has been used for the early management of such cases. A 10‐year‐old female with no significant medical and family history presented with the chief complaint of forward placement of lower front teeth on biting. Extraoral examination revealed a mesoprosopic face, a prominent lower lip, and a shallow mentolabial sulcus. Facial profile was straight at rest and concave at maximum intercuspation. Intraoral examination revealed a Class III incisor relationship with premature contact between 21 and 31, causing a forward path of closure of the mandible. The patient had a reverse overjet of 2 mm, an overbite of 5 mm, and a bilateral Super‐class I molar relationship at maximum intercuspation. Lateral cephalogram analysis revealed a mild skeletal class III denture base (ANB = 0°, Wits = −4 mm) due to a prognathic mandible (SNB = 82°). The treatment objectives included elimination of the premature contact, establishment of a positive overjet, and improvement of the facial profile. A Reverse Twin Block appliance was planned and prescribed for full‐time wear for 8 months. At the end of treatment, the patient had a Class I incisor relationship, straight facial profile, Class I molar relationship on the left side, and Super‐class I molar relationship on the right side. The Reverse Twin Block is a simple and well‐tolerated appliance that can effectively correct developing Class III malocclusion in carefully selected cases.